In vitro Conversion of Vinyl to Formyl Groups in Naturally Occurring Chlorophylls - Loughlin, Patrick C. (Nature Publishing Group, 2014)
The chemical structural differences distinguishing chlorophylls in oxygenic photosynthetic organisms are either formyl substitution (chlorophyll b, d, and f) or the degree of unsaturation (8-vinyl chlorophyll a and b) of a side chain of the macrocycle compared with chlorophyll a. We conducted an investigation of the conversion of vinyl to formyl groups among naturally occurring chlorophylls. We demonstrated the in vitro oxidative cleavage of vinyl side groups to yield formyl groups through the aid of a thiol-containing compound in aqueous reaction mixture at room temperature. Heme is required as a catalyst in aqueous solution but is not required in methanolic reaction mixture. The conversion of vinyl- to formyl- groups is independent of their position on the macrocycle, as we observed oxidative cleavages of both 3-vinyl and 8-vinyl side chains to yield formyl groups. Three new chlorophyll derivatives were synthesised using 8-vinyl chlorophyll a as substrate: 8-vinyl chlorophyll d, [8-formyl]-chlorophyll a, and [3,8-diformyl]-chlorophyll a. The structural and spectral properties will provide a signature that may aid in identification of the novel chlorophyll derivatives in natural systems. The ease of conversion of vinyl- to formyl- in chlorophylls demonstrated here has implications regarding the biosynthetic mechanism of chlorophyll d in vivo.